Detection of Helicobacter pylori in bladder biopsy specimens of patients with interstitial cystitis by polymerase chain reaction - ATUĞ, ÖZLEN (SPRINGER, 2004)
The cause of interstitial cystitis (IC) is still unknown. Several features suggest that it may be an infectious disease and it has compelling similarities to chronic gastritis. The identification of Helicobacter pylori as the cause of chronic gastritis focused attention on this organism. Many studies have been done investigating the role of H. pylori in the etiology of IC. Previous studies mostly determined the presence of H.pylori with antibodies in the serum samples of IC patients, but these methods may lead to false positive or negative results. We therefore investigated the presence of H.pylori in bladder biopsy specimens by using polymerase chain reaction (PCR), which is accepted as the most sensitive and specific test for detecting this organism. A total of 32 patients with IC were enrolled into the study. The PCR assay was performed on cold cup bladder biopsies of IC patients. Both positive and negative controls were included in each set of PCR reactions. Gastric biopsy specimens of peptic ulcer patients with proven H. pylori infection were used as positive controls. Bladder biopsies of all IC patients were negative for H. pylori DNA. PCR showed the presence of H. pylori in the positive controls in each cycle demonstrating that the PCR assay was working properly. Thus, there is no evidence that IC is the result of H. pylori infection. This study does not negate the possibility that other infectious agents may play a role in the etiology of IC.
Keywords: polymerase chain reaction; interstitial cystitis; Helicobacter pylori; PCR; AMPLIFICATION; CULTURE; FECES